Human Urinary Soluble Thrombomodulin (MR-33) Improves Disseminated Intravascular Coagulation without Affecting Bleeding Time in Rats: Comparison with Low Molecular Weight Heparin - Takahashi, Yasuo; Hosaka, Yoshitaka; Imada, Kazunori; Adachi, Takehiro; Niina, Hiromi; Watanabe, Mitsutoshi; Mochizuki, Hidenori (Thrombosis and Haemostasis, 1997)
We compared the antithrombotic and hemorrhagic effects of naturally existing human urinary soluble thrombomodulin (MR-33) with those of low molecular weight heparin (LMW-heparin) in rats. In in vitro experiments, MR-33 prolonged APTT in a dose-dependent fashion; its effect in this respect was as potent as that of LMW-heparin, but it was less potent than unfractionated heparin (UF-heparin). MR-33 was effective on endotoxin- or thromboplastin-induced disseminated intravascular coagulation (DIC) in rats. In both DIC models, infusion of MR-33 improved hematological abnormalities compatible with DIC in a dose-dependent fashion without excessive prolongation effect on APTT. Although LMW-heparin and UF-heparin also improved both DIC models, excessive prolongation of APTT was observed at high doses. It is well-known that the excessive prolongation of APTT with antithrombotic drugs like heparins is an index for hemorrhage, which is a major side effect in the treatment of DIC. We therefore further compared the antithrombotic (Benefit: dose required for 50% inhibition of fibrinogen decrease: ED50) and hemorrhagic (Risk: minimum dose required for significant prolongation of bleeding time) effects of MR-33 and LMW-heparin in the thromboplastin-induced DIC model. As a result, Benefit-Risk ratio was 1:27 for MR-33 and 1:3 for LMW heparin. These results indicate that MR-33 may be a clinically useful antithrombotic agent with reduced risk for hemorrhage compared with LMW-heparin.